Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the main characteristics and causes of Lithuania's inequality differentials relative to peers, and suggests policies that may reduce them. Although Lithuania has recovered well from the 2008-09 crisis and developmental indicators look reasonably good, it features one of the highest levels of income inequality in the European Union. Low living standards, modest public expenditure on social protection, limited tax progressivity, and high income volatility are the main causes of income inequality. More recently, Lithuania has taken some moderate steps to address income inequality and to improve the condition of low-wage earners through large minimum wage hikes.